Cross-species biosynthesis of maytansine in Maytenus serrata12. Issue 12 (25th January 2016) - Kusari, Parijat; Kusari, Souvik; Eckelmann, Dennis; Zühlke, Sebastian; Kayser, Oliver; Spiteller, Michael
Abstract : Endophytic bacterial communities of Cameroonian Maytenus serrata were investigated using genome mining and bioanalytical approaches to elucidate the source of maytansine biosynthesis. Abstract : Endophytic bacterial communities harboring different tissues of Maytenus serrata originating from Cameroon were investigated using targeted genome mining techniques coupled to bioanalytical approaches to elucidate the source of maytansine biosynthesis. It was revealed that the host plant, along with its cryptic endophytic microflora, produces the biosynthetically unique core structural moiety 3-amino-5-hydroxybenzoic acid (AHBA) that serves as the unique starter unit for maytansine biosynthesis. However, the biosynthetic step of halogenase-mediated incorporation of chlorine, which is missing in the host plant, is accomplished by the culturable stem endophytic bacterial community. Our results provide new insights into plant-endophyte communication for the biosynthesis of maytansine.